RETRACTED: Systemic Hepatic-Damage Index for Predicting the Prognosis of Hepatocellular Carcinoma after Curative Resection - Gao, Xing-hui; Zhang, Shuang-shuang; Chen, Hao; Wang, Yu-Hui; Yuan, Chun-Hui; Wang, Fu-Bing (Frontiers in Physiology, 2017)
ABSTRACT Purpose: We developed a novel systemic hepatic-damage index (SHI) based on serum total cholesterol and high density lipoprotein levels and determined its prognostic significance in hepatitis B virus-related hepatocellular carcinoma (HBV-HCC) patients undergoing resection. Experimental Design: The SHI was analyzed in the training cohort of 188 HBV-HCC patients and in the validation cohort of 177 HBV-HCC patients. The systemic immune-inflammation index (SII) scores in the validation cohorts were measured. Area under the receiver operating characteristic curve (AUC) was used to explore the prediction accuracy in HCC patients. Results: An optimal cutoff point for the SHI of 2.84 stratified the HCC patients into high SHI (>2.84) and low SHI (≤2.84) groups in the training cohort. Univariate and multivariate analyses revealed the SHI was an independent predictor for overall survival and relapse-free survival, and prognostic for patients with negative a-fetoprotein and Barcelona Clinic Liver Cancer stage 0+A. The AUCs of the SHI for survival and recurrence were higher than other conventional clinical indices. Low SHI significantly correlated with vascular invasion. The SII scores were significantly higher in patients with low SHI compared with those with high SHI. HCC patients in SHI≤2.84 group had shorter recurrence time and lower survival rate than HCC patients in SHI >2.84 group. Conclusion: The SHI was a powerful biomarker for assessing HCC prognosis, and improving SHI level in HCC patients is a promising therapeutic strategy decisions. The poor outcome in HBV-HCC patients with low SHI scores might increase SII scores, increasing the possibility of recurrence and metastasis.